Individual and cumulative impacts of fire emissions and tobacco consumption on wildland firefighters’ total exposure to polycyclic aromatic hydrocarbons - Oliveira, Marta (2019)
There is limited information about wildland firefighters' exposure to polycyclic aromatic hydrocarbons (PAHs), being scarce studies that included the impact of tobacco consumption. Thus, this work evaluated the individual and cumulative impacts of firefighting activities and smoking on wildland firefighters' total exposure to PAHs. Six urinary PAH metabolites (1-hydroxynaphthalene (1OHNaph), 1-hydroxyacenaphthene (1OHAce), 2-hydroxyfluorene (2OHFlu), 1-hydroxyphenanthrene (1OHPhen), 1-hydroxypyrene (1OHPy), and 3-hydroxybenzo[a]pyrene (3OHB[a]P)) were quantified by high-performance liquid chromatography with fluorescence detection. Firefighters from three fire stations were characterized and organized in three groups: non-smoking and non-exposed to fire emissions (NSNExp), smoking non-exposed (SNExp), and smoking exposed (SExp) individuals. 1OHNaph+1OHAce were the most predominant OH-PAHs (66-91% ∑OH-PAHs), followed by 2OHFlu (2.8-28%), 1OHPhen (1.3-7%), and 1OHPy (1.4-6%). 3OHB[a]P, the carcinogenicity PAH biomarker, was not detected. Regular consumption of tobacco increased 76-412% ∑OH-PAHs. Fire combat activities promoted significant increments of 158-551% ∑OH-PAHs. 2OHFlu was the most affected compound by firefighting activities (111-1068%), while 1OHNaph+1OHAce presented the more pronounced increments due to tobacco consumption (22-339%); 1OHPhen (76-176%) and 1OHPy (20-220%) were the least influenced ones. OH-PAH levels of SExp firefighters were significantly higher than in other groups, suggesting that these subjects may be more vulnerable to develop and/or aggravate diseases related with PAHs exposure.